Neurological Recovery in Traumatic Spinal Cord Injury Patient with Delayed Surgical Intervention - Mochamad Targib Alatas (Neurologico Spinale Medico Chirurgico, 2018)
Early surgical treatment for traumatic spinal cord injury (SCI) patients has been proven to yield better improvement on neurological state, and widely practiced among surgeons in this field. However, it is not always affordable in every clinical setting. It is undeniable that surgery for chronic SCI has more challenges as the malunion of vertebral bones might have initiated, thus requires more complex operating techniques. In this case series, we report 7 patients with traumatic SCI whose surgical intervention is delayed due to several reasons. Initial motoric scores vary from 0 to 3, all have their interval periods supervised between outpatient clinic visits. On follow up they demonstrate significant neurological development defined by at least 2 grades motoric score improvement. Physical rehabilitation also began before surgery was conducted. These results should encourage surgeons to keep striving for the patient’s best interest, even when the injury has taken place weeks or even months before surgery is feasible because clinical improvement for these patients is not impossible.